The trade union situation in Sweden - International Labour Office (Geneva : La tribune de geneve, 1961)
This book contain a factual surveys report by the International Labour Office in 1959 about Sweden. Their purpose is to promote social justice in all the countries of the world.
Includes bibliographical footnotes.
hza 20/02/2019
Loans
Keywords: Labor unions; Sweden